Structural properties of the peroxiredoxin AhpC2 from the hyperthermophilic eubacterium Aquifex aeolicus - Liu, Wenxia; Liu, Aijun; Gao, Hailong; Wang, Quan; Wang, Limin; Warkentin, Eberhard; Rao, Zihe; Michel, Hartmut; Peng, Guohong (Biochimica et biophysica acta. General subjects, 2018)
Peroxiredoxins (Prxs) are thiol peroxidases that scavenge various peroxide substrates such as hydrogen peroxide (H2O2), alkyl hydroperoxides and peroxinitrite. They also function as chaperones and are involved in signal transduction by H2O2 in eukaryotic cells. The genome of Aquifex aeolicus, a microaerophilic, hyperthermophilic eubacterium, encodes four Prxs, among them an alkyl hydroperoxide reductase AhpC2 which was found to be closely related to archaeal 1-Cys peroxiredoxins. We determined the crystal structure of AhpC2 at 1.8 Å resolution and investigated its oligomeric state in solution by electron microscopy. AhpC2 is arranged as a toroid-shaped dodecamer instead of the typically observed decamer. The basic folding topology and the active site structure are conserved and possess a high structural similarity to other 1-Cys Prxs. However, the C-terminal region adopts an opposite orientation. AhpC2 contains three cysteines, Cys49, Cys212, and Cys218. The peroxidatic cysteine CP49 was found to be hyperoxidized to the sulfonic acid (SO3H) form, while Cys212 forms an intra-monomer disulfide bond with Cys218. Mutagenesis experiments indicate that Cys212 and Cys218 play important roles in the oligomerization of AhpC2. Based on these structural characteristics, we proposed the catalytic mechanism of AhpC2. This study provides novel insights into the structure and reaction mechanism of 1-Cys peroxiredoxins. •AhpC2 is arranged as a circular dodecamer both in crystals and in solution.•Tube-like higher-order assemblies in solution were observed.•Peroxidatic Cys49 was hyperoxidized.•Cys212 and Cys218 form an intramonomeric disulfide bond.•The C-terminal domain of AhpC2 adopts an opposite orientation.